PNEUMOCOCCAL VACCINE VACCINATION IN CHILDREN WITH CONGENITAL HEART DEFECTS (American Journal of Technology and Applied Sciences, 2024)
193 vaccinated children were observed for 1.5 years. At the age of 2–6 months, 30% of premature and 46% of children with congenital heart defects were vaccinated with the PCV7/PCV13 vaccine; at the age of 7–11 months, 52 and 40%, respectively. In 65% of cases, the PCV7/PCV13 vaccine was administered together with other vaccines in the national preventive vaccination schedule. The frequency of general post-vaccination reactions (increase in body temperature from 37.6 to 38.0°C) was 4%; no local reactions were recorded. No other adverse events were noted in the post-vaccination period.